An in vitro study on the cleaning ability on the root canal irrigation techniques using two rotary niti systems - Ahmed Abou Elkheir , Amer Sobhy (2013)

(untitled)
Aim: To determine and compare the cleaning efficacy of two contemporary irrigation systems with conventional irrigation needles using two different rotary NiTi systems. Methods: 144 single rooted extracted human permanent teeth were divided randomly into four groups: EndoVac irrigation system, NaviTip FX irrigation needle, Conventional 25G needle and control. The groups were compared using TF and RaCe rotary systems. Four-micron-thick serial sections were prepared at 1.5 and 3.5mm from the apical foramen and the images were captured using optical microscopy and analyzed using Mirax software. The statistical analysis was performed using Kruskal-Wallis Test (p < 0.05) followed by intergroup comparison using Mann-Whitney Test (p < 0.008). Results: While the cleaning ability of EndoVac irrigation system was significantly better than conventional needle irrigation using both TF and RaCe rotary systems at 3.5 and 1.5mm (p < 0.008), there is no significant difference between NaviTip FX needle and conventional needle irrigation at both levels. With the exception of the cleaning ability at 1.5mm using TF, there is no significant difference between EndoVac system and NaviTip FX needle (p > 0.008). At both levels, the cleaning ability of TF and RaCe rotary systems with all irrigation systems was not significantly different. Conclusions: EndoVac irrigation system has better cleaning ability than NaviTip FX and conventional needle with both TF and RaCe rotary NiTi systems, especially at 1.5mm from the apical foramen. TF and RaCe rotary systems have similar cleaning ability with all irrigations systems.